1989
DOI: 10.1128/cmr.2.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease and the mycobacterioses: a review and comparison of two disease entities

Abstract: Crohn's disease is a chronic granulomatous ileocolitis, of unknown etiology, which generally affects the patient during the prime of life. Medical treatment is supportive at best, and patients afflicted with this disorder generally live with chronic pain, in and out of hospitals, throughout their lives. The disease bears the name of the investigator who convincingly distinguished this disease from intestinal tuberculosis in 1932. This distinction was not universally accepted, and the notion of a mycobacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(111 citation statements)
references
References 180 publications
1
107
0
3
Order By: Relevance
“…The microbial sensing proteins involved in innate immunity recognise conserved and often structural components of microorganisms. Published data has strengthened the association of MAP with Crohn's disease already for two decades (Chiodini et al, 1984(Chiodini et al, , 1986(Chiodini et al, , 1989HermonTaylor et al, 2000;Autschbach et al, 2005;Sechi et al, 2005). Crohn's disease affects hundreds of thousands of people around the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial sensing proteins involved in innate immunity recognise conserved and often structural components of microorganisms. Published data has strengthened the association of MAP with Crohn's disease already for two decades (Chiodini et al, 1984(Chiodini et al, , 1986(Chiodini et al, , 1989HermonTaylor et al, 2000;Autschbach et al, 2005;Sechi et al, 2005). Crohn's disease affects hundreds of thousands of people around the world.…”
Section: Discussionmentioning
confidence: 99%
“…The Colloquium also stated that it can be extremely difficult to prove that a pathogen is the cause of the chronic disorder when the onset of disease begins some time after the exposition. Often times it is not practical or even possible to use Koch's postulates to prove the infectious nature of chronic illnesses (Carbone et al, 2005) MAP and other agents (Clostridium spp., Campylobacter jejuni, Campylobacter feacalis, Listeria monocytogenes, Brucella abortus, Yersinia pseudotuberculosis, Yersinia enterocolica, Klebsiella spp., Chlamydia spp., Eubacterium spp., Peptostreptococcus spp., Bacteroides fragilis, Enterococcus feacalis, and Escherichia coli) are suspected to be possible triggers of Crohn's disease (Carbone et al, 2005), a chronic autoimmune inflammatory bowel disease with similar pathological changes to paratuberculosis (Chiodini, 1989). MAP cells contain peptidoglycans and heat shock proteins, which are able to initiate the inflammatory changes in the intestine (Elzaatari et al, 1995;Chamaillard et al, 2003).…”
mentioning
confidence: 99%
“…Oral inoculation of one of the strains into a newborn goat produced a granulomatous ileocolitis after 5 months, and the authors concluded that the isolates were strains of M. paratuberculosis or a biovariant that plays an etiologic role in some cases of CD. Interestingly, M. paratuberculosis causes Johne's disease, an intestinal disorder in ruminants such as cattle, horse and goat that resembles CD both clinically and histologically (34). Other studies reported increased titers of antibodies to M. paratuberculosis antigens in CD patients (35)(36)(37).…”
Section: Bacterial Agents In Crohn's Diseasementioning
confidence: 98%
“…M. avium subsp. paratuberculosis, which is very closely related to other M. avium subspecies, is a specific pathogen able to cause chronic inflammation of the intestine in ruminants, monogastrics such as dogs and pigs, and in subhuman primates (Larsen et al, 1971 ;McClure et al, 1987 ;Chiodini, 1989 ;Cocito et al, 1994). Our understanding of the genetic basis for this pathogenicity in M. avium subsp.…”
Section: Abbreviation : Mpil Multiplex Pcr Of Is900 Locimentioning
confidence: 99%